Special aspects of intergenerational intra-family conflicts during the pandemic - L. M. Grishina (Вестник университета, 2021)
The article deals with intergenerational conflicts within the family during the COVID-19 pandemic. The author reveals the topic of small groups isolation in the professional sphere: sailors, cosmonauts, polar explorers, members of long research expeditions. The topic of isolation is not new to psychology, since scientists in the middle of the last century faced this problem when they began to send expeditions to the poles, astronauts into space, etc. It analyses articles on the subject of isolation during the pandemic and reveals a mixed view of how families behave during this difficult time for society.